Plasma-based techniques applied to the determination of 17 elements in partitioned top soils - Morales del Mastro, Anabella Mabel; Londonio, Juan Agustín; Jiménez Rebagliati, Raúl Alberto Jorge; Pereyra, Marcelo Tomas; Dawidowski, Laura Elena; Gómez, Darío; Smichowski, Patricia Nora (Elsevier Science, 2015)
Fil: Morales del Mastro, Anabella Mabel. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín. Instituto de Investigación e Ingeniería Ambiental; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina